A longitudinal study of the moderating effects of social capital on the relationships between changes in human capital and ikigai among Japanese older adults. Issue 2 (11th December 2018) - Fukuzawa, Ai; Katagiri, Keiko; Harada, Kazuhiro; Masumoto, Kouhei; Chogahara, Makoto; Kondo, Narihiko; Okada, Shuichi
Abstract : Ikigai, one of the indices of well‐being, tends to decline with age because resources relating to ikigai decline. However, there are individual differences in this decline. This study tested for maintenance of ikigai among Japanese elderly, using a longitudinal study investigating the moderating role of social capital on the effects of changes in human capital on ikigai . We conducted a panel survey targeting 1, 068 people ( M age = 73.01 years) in 2013, and 686 people in 2017. The variables were ikigai, changes in human capital (self‐rated financial status, physical health) and social capital (social networks, trust in others), educational level, and control variables. Multiple regression analyses revealed the interaction effects of changes in physical health and changes in social networks (strong ties, weak ties) on follow‐up ikigai . Post hoc analyses indicated that declines in physical health predicted declines in ikigai among those whose social networks (strong ties and weak ties) had declined in the 4‐year study, but these relationships were not significant among those whose social networks had increased. The results suggest that older adults can weaken the adverse effect of a decline in human capital on ikigai by maintaining or increasing social networks.